FUNCTIONAL AUTONOMY OF ELDERLY WHO LIVES AT PARQUE DAS ROSAS- BARRA DA TIJUCA; RIO DE JANEIRO (Fiep Bulletin - online, 2015)
The present study aimed to conduct a battery of tests for evaluating the functional autonomy of the elderly. The subjects participants totaled 13 elderly individuals, from 60 years (average of 70.15 ± 9.33 years) of both sexes. The volunteers were submitted to the Protocol group of Latin American Development to maturity (GDLAM) with gauging of arterial pressure pre-and post-exercise, were evaluated variables of stature and body weight to calculate body mass index (BMI), waist circumference and hip circumference to calculate waist hip ratio (WHR). The results showed that the volunteers evaluated feature overweight (both sexes), the male evaluated presented moderate risk and evaluated presented high female laughter of heart disease by calculating the WHR, the evaluated for both sexes showed pressure within acceptable standards of pre-and post-test. GDLAM protocol tests were applied in all volunteers having an overall average considered weak according to the standard. The results obtained from the BMI of evaluated showed that most of them are overweight, this variable is not only on the physical exercise frequency, but also the lifestyle of the elderly. The results obtained from the GDLAM Protocol suggest that the functional autonomy of the elderly characterized low average in the population of the region, which was expected, since the average age of volunteers was 13 ± 70.15 years.
Keywords: Elderly; Functional autonomy; GDLAM.